The rise of nine eaudiobook - Lore, Pittacus (Lorien Legacies, 2012)
The third book of the #1 New York Times bestselling I Am Number Four series! The Mogadorians who destroyed the planet Lorien continue to hunt for the Garde, the small group of Loric survivors who have taken refuge on Earth. During a dangerous mission at a Mog base in West Virginia, John found and rescued the brutish Nine. But even with their combined powers, special abilities known as Legacies, the pair barely escaped with their lives. And in the process, John's best friend, Sam Goode, was lost and taken captive by the enemy. In order to save him—and our world—John and Nine must join forces with Six and Seven who have been battling the Mogs in Spain, and who are now trying to locate Number Eight in India. The Garde must come together before it is too late. They are Lorien and Earth's only hope. Michael Bay, director of Transformers, raved: "Number Four is a hero for this generation." This epic young adult series is perfect for fans of action-packed science fiction like The Fifth Wave series by Rick Yancey, The Maze Runner series by James Dashner, and Orson Scott Card's Ender's Game. The battle for Earth's survival wages on. Read the rest of the series: #4: The Fall of Five, #5: The Revenge of Seven, #6: The Fate of Ten, and #7: United as One. Don't miss the first book in the brand new I Am Number Four spin-off series: Generation One.